Harnessing Virtual Reality to Influence Attitudes Toward Beef Consumption: The Role of Empathy in Dietary Interventions - Chia-I Hou; Jiun-Hao Wang; Kun-Sun Shiao; Che Cheng (Foods)
The excessive consumption of red meat, such as beef, is a growing global health concern linked to increased risks of cancer and cardiovascular diseases. The health consequences associated with red meat consumption were estimated to cost USD 285 billion globally in 2020, accounting for approximately 0.3% of total health expenditures that year. Understanding the psychological mechanisms behind food choices is crucial for changing consumption habits, fostering healthy behaviors, and achieving sustainable dietary patterns. To address these challenges, this study utilizes virtual reality (VR) as a persuasive tool to examine how empathy, as a psychological mechanism, influences the intention to reduce beef consumption and its impact on dietary attitudes. Using an experimental design with 142 participants, the study found that in the VR context, individuals with higher empathy scores experienced a stronger sense of presence, significantly influencing their attitudes toward beef consumption, mediated by the change in anti-beef-eating attitude (p = 0.029). This suggests that VR can serve as an effective medium to reduce individuals’ willingness to consume beef and consequently prevent health risks associated with excessive meat intake. This study also highlights the importance of considering individual empathy levels when designing VR interventions to maximize their effectiveness and promote healthier dietary habits, ultimately improving public health. However, one limitation of this study is that it only assessed short-term changes in attitudes following the VR intervention, without incorporating long-term follow-ups to determine if these changes are sustained over time.